2016
DOI: 10.1016/j.amepre.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-Cessation Interventions for Urban Hospital Patients

Abstract: Introduction Hospitalization is a unique opportunity for smoking cessation, but prior interventions have measured efficacy with narrowly defined populations. The objective of this study was to enroll smokers admitted to two “safety net” hospitals and compare the effectiveness of two post-discharge cessation interventions. Design Randomized comparative effectiveness trial. Setting/participants At two New York City public hospitals, every hospitalized patient identified as a smoker (based on admission record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 27 publications
1
25
0
4
Order By: Relevance
“…Thus, the proportion of participants ultimately reached by quitline counseling was very small due to both low rates of referral and attrition across the phases of treatment initiation. These findings are similar to Sherman et al (2016), who reported similar difficulties in reaching hospitalized patients for post-discharge telephone counseling, with only 51% receiving at least one call. It is also possible that referral to the quitline, although evidence-based (Stead, Hartmann-Boyce, Perera, & Lancaster, 2013) and cost-effective (Hollis et al, 2007), may not be the optimal treatment approach for all hospitalized Veterans.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, the proportion of participants ultimately reached by quitline counseling was very small due to both low rates of referral and attrition across the phases of treatment initiation. These findings are similar to Sherman et al (2016), who reported similar difficulties in reaching hospitalized patients for post-discharge telephone counseling, with only 51% receiving at least one call. It is also possible that referral to the quitline, although evidence-based (Stead, Hartmann-Boyce, Perera, & Lancaster, 2013) and cost-effective (Hollis et al, 2007), may not be the optimal treatment approach for all hospitalized Veterans.…”
Section: Discussionsupporting
confidence: 85%
“…Each trial compared a post-discharge intervention to usual care. The interventions included a web-based program [14], interactive voice-response (IVR) support [15], staff-provided counseling [16], quitline counseling [17, 18], and provision of nicotine patches [18]. …”
Section: Methodsmentioning
confidence: 99%
“…Trials conducted in Birmingham, Alabama [14]; Boston, Massachusetts [15]; Kansas City, Kansas [17]; New York, New York [16]; and San Diego and Davis, California [18] used salivary cotinine to biochemically verify self-reported smoking abstinence at 6-months after randomization using a shared protocol. This shared protocol was designed to yield high return rates and collect comparable data for pooled analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of the CHART study including recruitment, participants, clinical sites, and intervention has been described previously (Grossman et al, 2012; Sherman et al, 2016). Briefly, the study was a randomized trial of adult current tobacco smokers who were admitted (to medicine, psychiatry, surgery, neurology, rehabilitation, pediatrics, and gynecology services) at two urban hospitals in New York City (Bellevue Hospital Center and the VA New York Harbor Healthcare System).…”
Section: Methodsmentioning
confidence: 99%